Individual, social and environmental predictors of physical activity in severe to morbid obese African American adolescents - Jeffrey J. Martin; Kathryn Brogan-Hartlieb; Angela J. Jacques-Tiura; Sylvie Naar-King; Deborah A. Ellis; Kai-Lin Catherine Jen (Karolinum Press, 2016)
The purpose of this study was to predict low, moderate, hard and very hard physical activity (PA) and walking/biking/jogging based PA. One-hundred and fifty-nine severe to morbid obese African-American adolescents participated. We predicted 8% of the variance in hard PA largely due to family support and 10% of the variance in very hard PA due to other support (e.g. counselor) and having home PA equipment. We also predicted 10% of the variance in walking/biking/jogging due to the walkability of the neighborhood. Our findings support the value of social support and environmental supports in helping obese African American adolescents increase PA.